PRINCE SAMUDRA'S TOMB AS A GROWTH GENERATOR FOR GUNUNG KEMUKUS SETTLEMENT IN SRAGEN REGENCY - Tri Hartanto; A Bamban Yuuwono; Danarti Karsono; Wahyu Prabowo (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2023)
The Javanese have many traditions, which illustrate that the Javanese or Javanese people in achieving their expectations are not enough just to work and pray, but there are other ways such as ritual efforts that are carried out based on their belief in various myths and the history of places considered sacredness that develops in society. One of the ritual places and has a strong mythical belief is the tomb of Prince Samudra on Gunung Kemukus, Pendem Village, Sumberlawang District, Sragen Regency, Central Java. This hill (mountain of cubes), there is the tomb of Prince Samudra, Nyai Ontrowulan and his servants. The Javanese people, especially the people around them, have a belief that the tombs are considered sacred. Then the community began to build houses and live around the tomb. The habit of people seeking blessings through the tradition of ngalap blessing, which is an activity to seek goodness from an essence, object or something that is considered by humans to have benefits and goodness, or seeking barakah (ngalap blessing) or other words